Problems of functioning of public administration mechanisms concerning the operational monitoring of the state of potentially dangerous objects - Shvedun, Viktoriia; Ihnatiev, Oleksandr; Postupna, Olena (Pressing Problems of Public Administration, 2022)
The problems concerning functioning of the modern Unified State Civil Protection System were studied, namely: the problems of functioning of a single information environment for the prompt supply of data on monitoring the state of potentially dangerous objects, only partial automation of processes concerning organization of the “dispatcher-applicant” dialogue during regulation passing information in the system of emergency assistance to the population using the single telephone number 112.An analysis of the mechanism of information flow in the system of emergency assistance to the population using the single telephone number 112 was carried out. It was shown that currently only part of the processes related to the organization of the “dispatcher-applicant” dialogue and the display of the operational situation on the electrified plan are automated.It has been proved that the territorial and functional subsystems of the Unified State Civil Protection System currently do not provide proper daily collection, processing, transmission and analysis of information about the probability of emergencies of man-made and natural nature and the development of preventive measures and proposals for their implementation.The need to improve the information mechanism of public administration of monitoring the state of potentially dangerous objects through the development of software complexes based on the functioning of intelligent systems, which are focused on processing unstructured data using Sentiment Analysis methods, has been confirmed.